Utilization of Giant Mimosa Stalk to Produce Effective Stick Spawn for Reducing Inoculum Costs in Economic Mushroom Farming Systems - Orlavanh Xayyavong; Worawoot Aiduang; Kritsana Jatuwong; Saisamorn Lumyong (Agriculture)
The high cost of mushroom spawn remains a critical constraint to economically viable mushroom cultivation, particularly for small-scale farmers. This study investigated four spawn types, including stick (giant mimosa stalks, GMS), sawdust, sorghum, and liquid culture as inoculum sources for 10 edible mushroom species. The results indicated that GMS stick spawn provides excellent conditions for the mycelial growth of seven species, outperforming other spawn types in terms of colonization rate and pinhead formation. Mushrooms grown on GMS substrate demonstrated rapid development, with full colonization occurring within 11 to 26 days and pinhead initiation between 18 and 47 days, depending on the species. Among the mushroom species tested, Schizophyllum commune exhibited the fastest growth, reaching full colonization in 11 days and forming pinheads after 18 days of inoculation. In comparison, Auricularia polytricha showed the slowest development. Economically, GMS spawn was the most cost-effective at 0.074 USD per unit, significantly lower than sawdust (0.24 USD), sorghum (0.29 USD), and potato dextrose broth (PDB; 2.80 USD). The conversion from PDB with GMS could reduce industrial inoculum costs from 35,000 USD to 600 USD annually. These findings demonstrate the potential of GMS as an effective, low-cost, and sustainable spawn option that can enhance mycelial growth and support eco-friendly farming practices.